2021
DOI: 10.1111/pace.14196
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cardiac resynchronization therapy in patients with chemotherapy‐induced cardiomyopathy

Abstract: Background Several chemotherapy agents are associated with the development of non‐ischemic cardiomyopathy (NIC). When chemotherapy‐induced cardiomyopathy (CHIC) is associated with left bundle branch block (LBBB) and a left ventricular ejection fraction (LVEF) 35% or lower, cardiac resynchronization therapy (CRT) is often utilized to improve cardiac function and relieve symptoms. Objective To determine the echocardiographic and clinical outcomes of CRT in patients with CHIC. Methods The study included 29 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The experience with CRT has largely been limited to adult cancer survivors. A retrospective study at the Mayo Clinic, including 29 patients with CTRCD who underwent CRT showed improvement in echo parameters within six to 18 months including increased LV EF and decreased LV diastolic and systolic dimensions [44]. Similar findings were seen in the MADIT-CHIC (Multicenter Automatic Defibrillator Implantation Trial-Chemotherapy-Induced Cardiomyopathy) study, an un-controlled prospective cohort study.…”
Section: Cardiac Resynchronization Therapy (Crt)supporting
confidence: 60%
“…The experience with CRT has largely been limited to adult cancer survivors. A retrospective study at the Mayo Clinic, including 29 patients with CTRCD who underwent CRT showed improvement in echo parameters within six to 18 months including increased LV EF and decreased LV diastolic and systolic dimensions [44]. Similar findings were seen in the MADIT-CHIC (Multicenter Automatic Defibrillator Implantation Trial-Chemotherapy-Induced Cardiomyopathy) study, an un-controlled prospective cohort study.…”
Section: Cardiac Resynchronization Therapy (Crt)supporting
confidence: 60%
“…Although cardiac dysfunction related to chemotherapy could be addressed with an interruption or discontinuation of chemotherapy, the cessation of chemotherapy in cancer patients may be related to poor clinical outcomes from the oncology standpoint. Furthermore, 0.5-2.5% of patients with chemotherapy-induced cardiomyopathy may have end-stage heart failure requiring a left-ventricular assist device or even heart transplant [9,10,[33][34][35]. Due to the possible poor trajectory, guidelines for prevention and surveillance of chemotherapy-induced cardiomyopathy are imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al (2019) reported improvement of LVEF from 28.5 ± 3.8% to 39.1 ± 7.1%, LVESV from 122.7 mL to 89 mL, LVEDV from 171 to 143.2 mL, and an improvement in NYHA class after CRT implantation. Ezzeddine et al (2021) and Patel et al (2022) demonstrated improved LVEF from 28 ± 8% to 38 ± 10% and 21.7 ± 7.4% to 30.4 ± 13.0%, respectively (Table 2).…”
Section: Study Outcomesmentioning
confidence: 98%
“…Chemotherapy is a crucial treatment option for various types of cancer, however, its use is associated with several adverse effects, one of which is chemotherapy‐induced cardiomyopathy (CIC) (Ezzeddine et al, 2021 ; Fadol et al, 2017 ; Patel et al, 2022 ; Rickard et al, 2010 ; Singh et al, 2019 ). CIC is characterized by a decline in left ventricular function, leading to symptoms of heart failure (Rickard et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation